2021
DOI: 10.3390/healthcare9050592
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Knowledge of Patients from Different Regions in the Kingdom of Saudi Arabia towards Oral Hygiene and Oral Hygiene Aids

Abstract: Aim: The present study aims to evaluate the perception and awareness of interdental aids in different regions of Saudi Arabia. Methods: A cross-sectional questionnaire-based study was conducted, in order to evaluate the perception and knowledge of patients towards oral hygiene products among the population of the Kingdom of Saudi Arabia. In total, 812 out of 1124 participants responded and completed the survey (response rate 72.2%). The data were collected using a self-administered structured questionnaire in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In a study by Bashir and Rizvi 10 the response for the survey on oral hygiene practices was 86 males and 107 females. The study by Alshahrani et al 11 the response for the survey on oral hygiene practices was 291 (35.9) male and 519 female (64.1). The distribution of the participants in the study by Alshahrani et al 11 were graduates 561 (69.3) and postgraduate were 60 (7.4) and in our study, there were 227 graduates and 19 postgraduates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Bashir and Rizvi 10 the response for the survey on oral hygiene practices was 86 males and 107 females. The study by Alshahrani et al 11 the response for the survey on oral hygiene practices was 291 (35.9) male and 519 female (64.1). The distribution of the participants in the study by Alshahrani et al 11 were graduates 561 (69.3) and postgraduate were 60 (7.4) and in our study, there were 227 graduates and 19 postgraduates.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Alshahrani et al 11 the participants frequency of cleaning the teeth was once by 274(33.8), twice by 272 (33.6) and whenever required cleaning was done by 90 (11.1). Alhammadi et al 3 reported in his study 28.2%, of the participants cleaned their teeth once 37.6%, twice, 28.4%, whenever required and 5.9% infrequently which is almost the same as our study in which the percentages are 24% once and 35.7% twice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suits the problem. However various studies showed that improper indication and use of interdental aids can cause mechanical periodontal tissue damage [12,16,24]. Our team has extensive knowledge and research experience that has translated into high quality publications [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Fig 4 Association Between Educational Qualification and Recommendation Criteria For Interdental Aids Usagementioning
confidence: 99%
“…Some researchers have reported promising results after using dental irrigators; while others have failed to demonstrate any beneficial effects [10]. Dental floss, toothpicks and single-strand brushes are recommended tools for interdental cleaning [11,12].…”
Section: Introductionmentioning
confidence: 99%